Outbreak of red leaf blotch caused by Dactuliochaeta glycines, on soybeans in Nigeria - Akem, C.N.; Akueshi, C.O.; Uwala, O.A.; Dashiell, Kenton E. (1992)
Red leaf blotch, caused by Dactuliochaeta glycines (R.B. Stewart) Hartman & Sinclair (2) (= Pyrenochaeta glycines R.B. Stewart), was observed on soybeans (Glycine max (L.) Merr.) at Bukuru, near Jos in the state of Plateau, Nigeria, in 1990. Over 80% of the plants in the 4¬ha nonirrigated, sandy loam field nursery showed symptoms. Dark red to brown lesions on primary leaf veins eventually enlarged and coalesced to form irregular blotches 5¬10 mm in diameter. Most blotches had ash¬gray centers with dark margins and some were surrounded by chlorotic halos. Pycnidia with setae clustered around the ostiole were observed within older blotches on the upper leaf surface. Premature senescence was common on severely infected plants. The pathogen was isolated on acidified potato-dextrose agar and lima bean agar; brown to black pycnidia, 156¬248 µm long X 87¬215 µm wide, formed only on lima bean agar. Plants of the cultivars TGx 1440¬2D and TGx 1636¬8F were inoculated in the greenhouse with an isolate of D. glycines. Symptoms were reproduced and the pathogen was reisolated. D. glycines has been a problem on soybeans mainly in Zambia and Zimbabwe, with yield losses of up to 50% (1). This is the first report of this important disease of soybeans under field conditions in Nigeria.